Experience from the field: Programming in a joint-use partnership library. Issue 3 (3rd July 2018) - Jordan, Christopher; Lawrence, Victor; Moran, Cristy
ABSTRACT: Librarians of the joint-use North Regional/Broward College (NR/BC) Library had sought opportunities to collaborate. Historically, challenges have arisen in programming for two distinct populations: seniors for the public library and the college library's students. In recent years, the library successfully capitalized on organizational changes and nationwide attention to media literacy and social justice to create and deliver several well-received collaborations. This article describes the environment in which these initiatives developed and provides tips on collaborations in- and out-side joint-use libraries. This article also addresses the dearth of professional literature on programming advantages in joint-use libraries.